2009
DOI: 10.1007/s12291-009-0046-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ingestion of copper bhasm on red cell indices, iron parameters and essential elements in chicks

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…; Sharma et al . ; Samanta et al . ), as Cp, which transports about 95% of Cu contained in blood, also takes part in iron metabolism (Meyer et al .…”
Section: Discussionmentioning
confidence: 99%
“…; Sharma et al . ; Samanta et al . ), as Cp, which transports about 95% of Cu contained in blood, also takes part in iron metabolism (Meyer et al .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it may result in muscle weakness, anaemia, bone alterations that resemble scurvy, defective connective tissue synthesis, impaired myelinisation of nerve tissues and neurological defects, altered lipid metabolism and cardiac malfunction (Mroczek-Sosnowska et al, 2013). Numerous studies have shown that Cu plays a significant and erythrocyte production Sharma et al, 2009;Samanta et al, 2011), which transports about 95% of Cu contained in blood, also takes part in iron metabolism (Meyer et al, 2001;Zerounian & Linder, 2002;Cherukuri et al, 2004). Cu increased haemoglobin, decreased plasma cholesterol and triglyceride significantly, decreased plasma proteins and its fraction did not change due to Cu supplementation (Rahman et al, 2001).…”
Section: Effects Nano-cuo On Physiological Responsementioning
confidence: 99%